DEVELOPMENT OF BAHASA INDONESIA TEACHING MODULE AT PHASE B BASED ON MERDEKA CURRICULUM - Triariani, Meti; Simbolon, Marlina Eliyanti; Wulandari, Isnaini (Journal Of Educational Experts (JEE), 2025)
This research backgrounded by the existence of a new policy on the implementation of the Independent Curriculum, namely the change from lesson plans to teaching modules. This study aims to develop a teaching module Bahasa Indonesia at phase B that is feasible and efective at SD Negeri 1 Purwainangun. This type of research is Research and Development (R&D). This research development stage refers to the Borg and Gall development model which has been grouped into three groups, namely preliminary studies, development, and testing and dissemination. The limited test subjects were two expert validators. The main test subjects were teachers and 20 grade IV students at SD Negeri 1 Purwawinangun, Kuningan, West Java. The data collection instrument used interview guidelines, product assessment questionnaires validators of material experts and media experts, as well as teacher response questionnaires. The data analysis technique of the validator's assessment results in the limited test uses Aiken's V statistics. The data analysis technique of the product effectiveness of the main test results uses student test results to determine the suitability of the product with the goal. To test the effectiveness using a paired sample test T-test. The results of the research on the limited test are that the teaching module Bahasa Indonesia at phase B according to the expert validator is feasible to use, as evidenced by the average Aiken's V score for the teaching module product which was 0.889 in the very high category. The effectiveness test of the teaching module products showed that the teaching module Bahasa Indonesia at phase B was able to improve the quality of learning in the classroom and improve student learning outcomes, as evidenced by the tcount value of 6.788 greater than the ttable value of 2.093. This shows that the product of the developed teaching module Bahasa Indonesia at Phase B can be said to be very feasible and effective to use.